2011
DOI: 10.1080/1475939x.2011.610930
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs and ICT: what can we learn from experienced educators?

Abstract: This paper contributes to a special edition of Technology Pedagogy and Education by looking at beliefs about knowing and learning held by 15 teacher educators with long standing involvement in the Association for Information Technology in Teacher Education (ITTE). Beliefs were challenging to identify but were ascribed to participants through examining accounts of practice on the basis of 'what they held true' about teaching and learning. The study uncovered a widely held core belief in knowing as constructivis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 31 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…In addition, these authors reported 135 independent and 8 dependent variables in their review. In recent years, researchers have adapted some of these theories to investigate their capabilities in understanding technology acceptance of users in education (e.g., Hammond, 2011;Teo, 2009;Teo, Koh, & Lee, 2011).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…In addition, these authors reported 135 independent and 8 dependent variables in their review. In recent years, researchers have adapted some of these theories to investigate their capabilities in understanding technology acceptance of users in education (e.g., Hammond, 2011;Teo, 2009;Teo, Koh, & Lee, 2011).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Thus, beliefs can refer to thoughts about the usefulness of ICT, to thoughts about one's ability to handle ICT applications, to thoughts about teaching, and to thoughts about learning (Ertmer 2005). In addition to thoughts about teaching and learning, Hammond (2011) distinguished beliefs about knowing. Voogt et al (2013) refer to beliefs about technology and pedagogical beliefs.…”
Section: Beliefsmentioning
confidence: 99%
“…But, as noticed above, there exists also a remarkable consensus among researchers as the majority of the research into teacher beliefs focusses on pedagogical beliefs and more specifically on beliefs about learner-versus teacher-centered education (e.g. Hammond 2011;Hermans et al 2008;Koh et al 2015;Lim and Chai 2008;Lin et al 2012;Sang et al 2010;Sang et al 2011;Way and Webb 2007). Mama and Hennessy (2013) categorize teacher beliefs according to beliefs about usefulness of ICT use under which also was subsumed encouraging "constructivist instead of traditional teaching" and "autonomous learning" (p. 383).…”
Section: Beliefsmentioning
confidence: 99%
“…Higgins & Moseley (, p. 204) describe two possible uses of ICT: the first, “retrospective” to accommodate an existing curriculum, and the second, forward looking and leading to radical changes in teaching and learning. The latter has tended to capture the imagination of teacher educators supporting the introduction of ICT into education (Hammond, ). Educators, while recognising the limitations of programmed instruction and often lukewarm on IWBs, have often seen technology as enabling a paradigm shift in teaching and learning.…”
Section: Why Has Ict Been Promoted?mentioning
confidence: 99%